2019
DOI: 10.2196/10008
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effectiveness of Engaging Patients and Their Families in the Three-Step Fall Prevention Process Across Modalities of an Evidence-Based Fall Prevention Toolkit: An Implementation Science Study

Abstract: BackgroundPatient falls are a major problem in hospitals. The development of a Patient-Centered Fall Prevention Toolkit, Fall TIPS (Tailoring Interventions for Patient Safety), reduced falls by 25% in acute care hospitals by leveraging health information technology to complete the 3-step fall prevention process—(1) conduct fall risk assessments; (2) develop tailored fall prevention plans with the evidence-based interventions; and (3) consistently implement the plan. We learned that Fall TIPS was most effective… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
87
0
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(111 citation statements)
references
References 15 publications
0
87
0
16
Order By: Relevance
“…This translated into a clinically significant patientcentered Fall TIPS intervention in all study units. 20 In the adjusted analysis, the overall fall rate in study units decreased from 2.92 falls per 1000 In the adjusted analysis, the overall injurious fall rate in study units decreased from 0.73 injurious falls per 1000 patient-days (95% CI, 0.59-0.92 falls per 1000 patient-days) before implementation to 0.48 injurious falls per 1000 patient-days (95% CI, 0.34-0.70 falls per 1000 patient-days) in the postintervention period. After adjustment for demographics in the Poisson regression model, study units achieved a 34% reduction in overall falls with injury in the postintervention period (adjusted RR, 0.66; 95% CI, 0.53-0.88; P = .003).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This translated into a clinically significant patientcentered Fall TIPS intervention in all study units. 20 In the adjusted analysis, the overall fall rate in study units decreased from 2.92 falls per 1000 In the adjusted analysis, the overall injurious fall rate in study units decreased from 0.73 injurious falls per 1000 patient-days (95% CI, 0.59-0.92 falls per 1000 patient-days) before implementation to 0.48 injurious falls per 1000 patient-days (95% CI, 0.34-0.70 falls per 1000 patient-days) in the postintervention period. After adjustment for demographics in the Poisson regression model, study units achieved a 34% reduction in overall falls with injury in the postintervention period (adjusted RR, 0.66; 95% CI, 0.53-0.88; P = .003).…”
Section: Resultsmentioning
confidence: 99%
“…Problem analysis: learn about the needs and preferences of patients and providers and other social-technical factors that relate to fall prevention 4. Implementation: conduct a pilot test of fall TIPS and compare for effectiveness in engaging patients and families in the 3-step fall prevention process 15,20 Laminated paper poster 2. Design and 3.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Recent studies have shown that adequate selfmanagement may minimize the impact of falls in older adults. [9][10][11][12][13][14][15][16] However, research is lacking on why some older adults engage in self-management actions and behaviors to prevent falls while others do not. 15 Research is needed to explore possible barriers and facilitators to engaging older patients in preventing falls post-hospitalization.…”
Section: Introductionmentioning
confidence: 99%